1948
DOI: 10.1021/ie50459a040
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stability of Molybdena-Alumina Dehydrocyclization Catalysts

Abstract: The heat stability in dry air of molybdena-alumina catalysts has been measured as a function of alumina type, alumina area, and molybdena concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1949
1949
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Ethylbenzene, toluene, 0-, m-, and p-xylenes (66) 3,3-Dimethylhexane........ Pt-carbon 1,1-Dimethylcyclohexane, toluene, m-xylene (79,80) 2,5-Dimethylhexane........ Active carbon, Fe-carbon p-Xylene Ce02-Al203; V203-A1203; Th02-Al203 Pd-Cr203; Ni-Cr203; Cu-Cr2ü3; Zn0-Cr203; Mo02-Cr203; Mn0-Cr203; Si02-Cr203; Aromatics (113,114) Aromatics (40,154) m-Xylene ( 91) Benzene (92) Toluene (40,54,65,69,105,111,113,114,132,145,154,159,160) Toluene (20,66,100,111,147,153,160) Toluene (20,153) Toluene (37,153) Toluene (54) Toluene (51,65,143,144,160) Toluene ( 75)…”
Section: Cr203-al203mentioning
confidence: 99%
“…Ethylbenzene, toluene, 0-, m-, and p-xylenes (66) 3,3-Dimethylhexane........ Pt-carbon 1,1-Dimethylcyclohexane, toluene, m-xylene (79,80) 2,5-Dimethylhexane........ Active carbon, Fe-carbon p-Xylene Ce02-Al203; V203-A1203; Th02-Al203 Pd-Cr203; Ni-Cr203; Cu-Cr2ü3; Zn0-Cr203; Mo02-Cr203; Mn0-Cr203; Si02-Cr203; Aromatics (113,114) Aromatics (40,154) m-Xylene ( 91) Benzene (92) Toluene (40,54,65,69,105,111,113,114,132,145,154,159,160) Toluene (20,66,100,111,147,153,160) Toluene (20,153) Toluene (37,153) Toluene (54) Toluene (51,65,143,144,160) Toluene ( 75)…”
Section: Cr203-al203mentioning
confidence: 99%
“…The dehydrocyclization activity of molybdenaalumina and chromiaalumina catalysts has been the subject of much research. Webb, Smith, and Ehrhardt (47) and Claussen and Wellmen (12) claim superiority of coprecipitated molybdena-alumina over the impregnated variety, although Russell and Stokes (34) indicated that, if not handled properly in process operation, its stability may be no greater. The dehydrocyclization activity of chromiaalumina catalysts has long been recognized as greater than that of molybdena-alumina at atmospheric pressure.…”
Section: General Methods Of Preparationmentioning
confidence: 99%
“…Russell and Stokes (91) investigated the heat stability of molybdena-alumina dehydrocyclization catalysts. The dehydrocyclization of n-heptane to toluene is increased as the catalysts are calcined at temperatures from 600°to 700°C ., while at higher calcination temperatures the activity is lowered.…”
Section: Catalytic Re-forming Chemical Conceptsmentioning
confidence: 99%